2022
DOI: 10.24002/kinerja.v26i2.6185
|View full text |Cite
|
Sign up to set email alerts
|

Financial Technology in Indonesia: Effect of Risk on Financial Performance in Peer-To-Peer Lending

Abstract: This study aims to acquire empirical evidence related to the effect of risk on financial performance in peer-to-peer lending in Indonesia. By exploring the financial statements throughout 2019-2020. The test uses a panel data regression model, the Common Effect Model as the selected estimation regression model. Financial risk is measured by Operating Income Operating Expenses (BOPO), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Capital Adequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Capital or capital in this research uses the Capital Adequacy Ratio (CAR). This ratio is effective when a bank experiences losses because it shows how capable the bank is of covering assets that experience a decrease in its capital adequacy (Putri & Wibisono, 2022).…”
Section: Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…Capital or capital in this research uses the Capital Adequacy Ratio (CAR). This ratio is effective when a bank experiences losses because it shows how capable the bank is of covering assets that experience a decrease in its capital adequacy (Putri & Wibisono, 2022).…”
Section: Capitalmentioning
confidence: 99%
“…This research uses the capital adequacy ratio (CAR), which measures a bank's resilience in facing risks that may arise. If the CAR is high, the bank has sufficient capital and financial resources to manage assets and pay off its obligations (Cahyani & Putri, 2018;Putri & Wibisono, 2022). It can be concluded that a high CAR value indicates that the bank has sufficient capital to carry out its operational activities, which can be a positive signal and can increase the demand or supply of stock prices.…”
Section: The Effect Of Capital On Stock Pricesmentioning
confidence: 99%